Phase 1/2 study of the safety and clinical activity of durvalumab in patients with non-small cell lung cancer (NSCLC) - Antonia, Scott J.; Jäger, Dirk (Annals of oncology, 2016)
© The Author 2016. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For permissions, please email: journals.permissionsoup.com.Background: High PD-L1 expression in lung tumors is associated with response to PD-L1-targeted treatment. Durvalumab, an anti-PD-L1 monoclonal antibody, was evaluated in patients with advanced solid tumors, including NSCLC, in a Phase 1/2 multicenter, open-label study (NCT01693562).Methods: Patients received durvalumab 10 mg/kg IV Q2W for up to 12 months or until unacceptable toxicity or disease progression. Safety was evaluated (CTCAE v4.03) through 90 days after last dose; confirmed response (RECIST v1.1) was based on investigator assessment. Retreatment was permitted only upon progression after 12 months of therapy in patients with disease control. Tumor PD-L1 expression was assessed using the Ventana PD-L1 IHC (SP263) assay.Results: As of 29 April 2016, 304 NSCLC patients received durvalumab; 144 (47%) had non-squamous and 160 (53%) had...
Gesehen am 09.11.2017